Metastasis at a tracheostomy site as the presenting sign of late recurrent breast cancer. Issue 11 (18th March 2013) - Rotolo, Nicola; Dominioni, Lorenzo; De, Lavinia; Conti, Valentina; La Rosa, Stefano; Imperatori, Andrea
<x xml:space="preserve">Abstract</x> Background Metastasis in a tracheostomy site occurs rarely, usually from head and neck primary tumors. Breast cancer relapse to a tracheostomy has not been described to date. Methods and Results A 71‐year‐old women presented with symptoms typical of central airway obstruction, 10 years after mastectomy for breast cancer. Fifteen months before admission, when cancer follow‐up was negative, she also had surgery for cerebral aneurysm and a tracheostomy. On admission, CT showed a solid mass infiltrating the tracheostomy tract and projecting into the airway. Tracheal obstruction palliation was achieved by laser resection of the endotracheal growth and stenting. Histology documented breast cancer metastasis. Conclusions Tracheostomy site metastasis was the presenting sign of late‐onset relapse of breast cancer. This case supports the concept of surgery‐driven interruption of micrometastatic cancer dormancy, in that the initial recurrence developed in a tracheostomy that was surgically created several years after resection of the primary tumor. © 2013 Wiley Periodicals, Inc. Head Neck, 35: E359–E362, 2013